Association Between Patient Activation and Medication Adherence in Patients With Stroke: A Cross-Sectional Study - Sui, Weijing; Wan, Li-hong (Frontiers in Neurology, 2021)
Background Medication adherence is key to secondary prevention in patients with stroke. Poor medication adherence can lead to recurrence, disability, or even death in stroke survivors. Patient activation is associated with increased healthy behaviors and improved clinical outcomes in many chronic diseases. However, the association between patient activation and medication adherence in patients with stroke remains unclear. Objective The study aimed to explore the influence of patient activation on the medication adherence of patients with stroke and to analyze the reasons for medication non-adherence. Materials and Methods A cross-sectional design with convenience sampling was used in this study. A total of 119 patients with stroke were recruited from a tertiary hospital in Guangzhou. A social-demographic and clinical data form, a self-developed medication adherence questionnaire, and the 13-item Patient Activation Measure (PAM-13) were used. Univariate analysis and multiple linear regression analyses with dummy variables were conducted to investigate the associations between medication adherence and patient activation. Data were analyzed with IBM® SPSS® version 25.0. Results The mean PAM-13 score in patients with stroke was 51.56±12.58. A low level of patient activation was reported by up to 66.4% of the patients. The self-reported medication adherence questionnaire score was 5.59±1.52. A low level of medication adherence was reported by up to 59.7% of the patients, while a moderate level was reported by 34.4%, and a high level was reported by only 5.9%. In the multiple stepwise regression analysis, patient activation was found to be an independent influencing factor of medication adherence in patients with stroke (p<0.05). Conclusion Medication adherence was poor in patients in Guangzhou, China following an ischaemic stroke. Patient activation as the independent influencing factor identified in this study will support healthcare givers to develop the tailored intervention to improve medication adherence among patients with stroke in China.